Formulasi Sediaan Sabun Mandi Padat dengan Zat Aktif Sari Buah Naga Merah (Hylocereuspolyrhizus) Asal Kabupaten Sidrap - Nurastuti Wulandari; Fitriana Bunyanis; Bulqisyah Umrina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to make a solid bath soap formulation with theactive substance of (Hycolereuspolyrhizus) origin of sidrap district. There are 3 concentration susedin this study, namely concentrationsof 10%, 15% and 20%. The result of this research is that in making soap with the additionof (Hycolereuspolyrhizus), it can produce soap that is solid and hard and doesnotsoftenata temperatureof 15-300C, using 3 concentrations, namely 10%, 15%, and 20%. The best formulais the formulation with a concentration of 15% and 20% which produces a yellowish and does nothavea strong odor.This happens because concentration sof 15% and 20% have more (Hycolereuspolyrhizus) so that the soap base is reduced.